Improvement of High School Students' Physics Problem Solving Skills Through Problem Based Learning Assisted by LKPD (Student Worksheets) - Simangunsong, Ika Trisni; Uskenat, Kristina; Damanik, Dede Parsaoran; Simangunsong, Ita Pratiwi; Purba, Andre Agachi (Universitas Pendidikan Mandalika, 2024)
This study employed classroom action research with the aim of enhancing students' physics problem-solving skills using Problem-Based Learning (PBL) supported by student worksheets (Lembar Kerja Peserta Didik/LKPD). The research targeted 10th-grade high school students focusing on the topic of Measurement. The methodology followed a cycle comprising four stages: planning, action, observation, and reflection. At the end of each cycle, evaluations were conducted using a validated test instrument consisting of four essay questions. The success criterion was set at a minimum of 70% of students achieving a mastery level, defined by a score of at least 65. During the pre-cycle phase, before applying PBL, the initial test results revealed no students achieved mastery, with an average problem-solving score of 54.67. Subsequently, two cycles of PBL implementation were carried out. In the first cycle, 15 students reached the mastery criterion, representing 41.17% improvement in problem-solving skills, with an average score of 63.75. Building on this progress, the second cycle was implemented, resulting in 29 students achieving mastery. This represented 80.05% of the class, categorized as a moderate improvement, with an average problem-solving score of 70.05. These findings indicate a significant enhancement in students' physics problem-solving abilities through the integration of PBL and LKPD. This approach effectively facilitated active student engagement and critical thinking, demonstrating its potential as an impactful instructional strategy in high school physics education.